The problem of teaching speech activities in a foreign language to international law students - A. Bochenkov; T. Ivanova (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article explores the challenges and methodologies involved in teaching speech activities in English to students specializing in International Law at the School of Law. Theproblems are further complicated by the conditions of distance learning, which, on the one hand, exacerbate the teaching process, but on the other hand, offer facilitation as distance learning, by its nature, enhances interaction between students and teachers, granting flexibility in terms of both spatial and temporal dimensions. Among the many means of communication utilized, Zoom stands out as a prominent service for organizing online classes. The key factor in optimizing language skills is the use of a student-centered model. The current level of development of students’ speaking skills in the target language does not meet modern educational requirements, which emphasizes the relevance of this issue. In the era of globalization, the main goal of teaching English is not just to master the language system or gain linguistic knowledge, but to master it as a means ofcommunication. Creating favorable conditions for the development of students’ communicative skills in a foreign language is one of the main tasks of the teacher. By recreating circumstances that are similar to those when native speakers acquire native language skills, students can immerse themselves in a similar environment, and this will contribute to the effective development of their speech skills.